Studi Bukaan Sinusoidal pada Balok Baja Castella - Dania Nissa; Aniendhita Rizki Amalia (Politeknik Negeri Jakarta, 2026)
Castella steel beams are among the most efficient solutions in steel construction; they can increase beam height, moment of inertia ( ), and section modulus ( ) without adding weight itself. Based on a previous study, sinusoidal openings have better structural performance than hexagonal openings due to their curved profile and minimal stress concentration. However, research on sinusoidal openings is still limited. This study uses the Finite Element Method (FEM) approach with ABAQUS software for a static load test. The numerical model was developed based on previous experimental studies and modified with variations in opening spacing of 100–300 mm (specimens A–E). The modeling was carried out on beams with spans of 2000 mm (short), 5000 mm (medium), and 10000 mm (long). The results of the study show that structural performance decreases as span length increases, with average load capacities of 140.14 kN, 116.99 kN, and 116.37 kN for short, medium, and long spans, respectively. Specimen D showed the highest ductility in all span variations. Based on the moment-curvature response and energy absorption, short-span beams performed the best, while long-span beams performed the worst. The span-to-beam height ratio recommendation is 0.56, because it has the best ductility performance.